Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) x12= x10
=> x12 - x10 = 0
x10.(x2-1) = 0
TH1: x = 0
TH2: x2 - 1 = 0
x2 = 1 => x thuộc {- 1 ; 1 }
Vậy x thuộc {-1 ; 0; 1}
b) 3x + 3x + 1 + 3x + 2 = 351
3x.(1 + 3 + 32) = 351
3x . 13 = 351
3x = 351 : 13 = 27
3x = 33
Vậy x = 3
c) x + 5 = 2x + 10
x - 2x = 10 - 5
-x = 5
x = -5
a.
\(x^{12}=x^{10}\)
\(x\in\left\{0;1;-1\right\}\)
b.
\(3^x+3^{x+1}+3^{x+2}=351\)
\(3^x+3^x\times3+3^x\times3^2=351\)
\(3^x\left(1+3+9\right)=351\)
\(3^x\times13=351\)
\(3^x=351\div13\)
\(3^x=27\)
\(3^x=3^3\)
\(x=3\)
c.
\(x+5=2x+10\)
\(x-2x=10-5\)
\(-x=5\)
\(x=-5\)
Chúc bạn học tốt
1)a)34-26-54=81-64-625=-608
ko hiểu b
2)a)(3x-1)2=(5/6)2=(-5/6)2
+)3x-1=5/6 =>x=11/18
+)3x-1=-5/6 =>x=1/18
b)(x+7)x-11(1-(x-7)23)=0
=>+)(x+7)x-11=0 =>x+7=0 =>x=-7
+)1-(x+7)23=0 =>(x+7)23=1 =>x+7=1 =>x=-6
a, đề sai
b) \(\left(x-3\right)^{10}=\left(x-3\right)^{30}\)
\(\Rightarrow\left\{{}\begin{matrix}x-3=-1\\x-3=0\\x-3=1\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=2\\x=3\\x=4\end{matrix}\right.\)
Vậy .....
c) \(\left(x+1,5\right)^8+\left(2,7-y\right)^{12}=0\)
Vì: \(\left\{{}\begin{matrix}\left(x+1,5\right)^8\ge0\forall x\\\left(2,7-y\right)^{12}\ge0\forall y\end{matrix}\right.\)
\(\Rightarrow\) để bt = 0
=>\(\left\{{}\begin{matrix}\left(x+1,5\right)^8=0\\\left(2,7-y\right)^{12}=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x+1,5=0\\2,7-y=0\end{matrix}\right.\)
=> \(\left\{{}\begin{matrix}x=-1,5\\y=2,7\end{matrix}\right.\)
Vậy.............